Generalizations of Euler numbers and polynomials - Qiu-Ming Luo; Feng Qi; Lokenath Debnath (International Journal of Mathematics and Mathematical Sciences)
The concepts of Euler numbers and Euler polynomials are generalized and some basic properties are investigated.